Efficacy of nebulized magnesium sulfate in the treatment of acute exacerbation of asthma in children - M. Ataul Haqq, Md. Hamidur Rahman, Selina Khanam and M.A. Mannan (Bangladesh Journal of Pharmacology, 2006)
A double blind randomized controlled trial was conducted to examine the efficacy of nebulized magnesium sulfate in the treatment of acute exacerbation of asthma in children. Thirty patients received nebulized salbutamol (0.15 mg/kg; minimum dose 2.5 mg) with 2.0 ml of isotonic magnesium sulfate solution and another 30 patients received same dose of salbutamol with 2.0 ml of normal saline on 3 occasions at 20 minute intervals. Mean percent of predicted peak expiratory flow rate (PEFR) detected in both group at 0 minute were not significantly different. But from 10 minute up to 60 minute, the values were significantly different among the groups. Mean respiratory rate at 0 and 10 minute were similar in both groups and from 20 up to 60 minute, respiratory rate improvement were significantly different. Arterial oxygen saturation (SaO2) at presentation was not significantly different. But from 10 min up to 60 minute differences were significant. With single dose of nebulization, in the magnesium sulfate with salbutamol group, by 20 minute almost all (29 out of 30) patient achieved at least 60% of predicted PEFR. Within this 20 minute, from control group none could achieve 60% of predicted PEFR. After 2nd dose of nebulization control group started achieving 60% PEFR value. Regarding response criteria, with 2nd dose of nebulization, at 30 and 40 minute 9 (30.0%) and 17 (56.7%) patient from magnesium sulfate with salbutamol group showed good response (PEFR ≥ 70% predicted). But within this first 40 minutes time, none could show good response in control group. With 3rd dose of nebulization all from magnesium sulfate group showed good response but even at 60 minute, 4 (13.3%) patient in control group failed to be included as good responder. So, it is evident that nebulization by isotonic magnesium sulfate solution with salbutamol provide early and better response as compared to conventional approach (salbutamol plus normal saline) in acute exacerbation of asthma in children.